The Effects of Two Influential Early Childhood Interventions on Health and Healthy Behaviors - Gabriella Conti; James J. Heckman; Rodrigo Pinto (Institute for the Study of Labor (IZA), 2015)
This paper examines the long-term impacts on health and healthy behaviors of two of the oldest and most widely cited U.S. early childhood interventions evaluated by the method of randomization with long-term follow-up: the Perry Preschool Project (PPP) and the Carolina Abecedarian Project (ABC). There are pronounced gender effects strongly favoring boys, although there are also effects for girls. Dynamic mediation analyses show a significant role played by improved childhood traits, above and beyond the effects of experimentally enhanced adult socioeconomic status. These results show the potential of early life interventions for promoting health.
Keywords: C12; C93; I12; I13; J13; J24; 330; health; early childhood intervention; social experiment; randomized trial; Abecedarian Project; Perry Preschool Project